Extracellular vesicle-guided in situ reprogramming of synovial macrophages for the treatment of rheumatoid arthritis. (July 2022) - Kim, Hyosuk; Back, Ji Hyun; Han, Geonhee; Lee, Su Jin; Park, Yae Eun; Gu, Man Bock; Yang, Yoosoo; Lee, Ji Eun; Kim, Sun Hwa
Abstract: Activation state of synovial macrophages is significantly correlated with disease activity and severity of rheumatoid arthritis (RA) and provides valuable clues for RA treatment. Classically activated M1 macrophages in inflamed synovial joints secrete high levels of pro-inflammatory cytokines and chemokines, resulting in bone erosion and cartilage degradation. Herein, we propose extracellular vesicle (EV)-guided in situ macrophage reprogramming toward anti-inflammatory M2 macrophages as a novel RA treatment modality based on the immunotherapeutic concept of reestablishing M1-M2 macrophage equilibrium in synovial tissue. M2 macrophage-derived EVs (M2-EVs) were able to convert activated M1 into reprogrammed M2 (RM2) macrophages with extremely high efficiency (>90%), producing a distinct protein expression pattern characteristic of anti-inflammatory M2 macrophages. In particular, M2-EVs were enriched for proteins known to be involved in the generation and migration of M2 macrophages as well as macrophage reprogramming factors, allowing for rapid and efficient driving of macrophage polarization toward M2 phenotype. After administration of M2-EVs into the joint of a collagen-induced arthritis mouse model, the synovial macrophage polarization was significantly shifted from M1 to M2 phenotype, a process that benefited greatly from the long residence time (>3 days) of M2-EVs in the joint. This superb in situ macrophage-reprogramming ability of EVs resulted in decreased joint swelling, arthritic index score and synovial inflammation, with corresponding reductions in bone erosion and articular cartilage damage and no systemic toxicity. The anti-RA effects of M2-EVs were comparable to those of the conventional disease-modifying antirheumatic drug, Methotrexate, which causes a range of toxic adverse effects, including gastrointestinal mucosal injury. Overall, our EV-guided reprogramming strategy for in situ tuning of macrophage responses holds great promise for the development of anti-inflammatory therapeutics for the treatment of various inflammatory diseases in addition to RA.